Trafficking of endoplasmic reticulum-retained recombinant proteins is unpredictable in Arabidopsis thaliana - De Meyer, Thomas; Depicker, Ann (Frontiers in Plant Science, 2014)
A wide variety of recombinant proteins has been produced in the dicot model plant, Arabidopsis thaliana. Many of these proteins are targeted for secretion by means of an N-terminal endoplasmic reticulum (ER) signal peptide. In addition, they can also be designed for ER retention by adding a C-terminal H/KDEL-tag. Despite extensive knowledge of the protein trafficking pathways, the final protein destination, especially of such H/KDEL-tagged recombinant proteins, is unpredictable. In this respect, glycoproteins are ideal study objects. Microscopy experiments reveal their deposition pattern and characterization of their N-glycans aids in elucidating the trafficking. Here, we combine microscopy and N-glycosylation data generated in Arabidopsis leaves and seeds, and highlight the lack of a decent understanding of heterologous protein trafficking.